8.2cardiac ion channelopathies in unexplained stillbirths. - Addison,S; Munroe,P; Mein,C; Cohen,M; Fowler,D; Sebire,NJ; Peebles,D; Taylor,A; Abrams,D; Thayyil,S (Arch Dis Child Fetal Neonatal Ed, 2014)
Although cardiac ion channelopathies are reported in up to 15% of sudden infant deaths, the prevalence in unexplained stillbirths is not known.